Das Ezechielbuch als Trauma-Literatur - Poser, Ruth. (Vetus Testamentum, Supplements, 2012)
The book of Ezekiel has long astonished its readership. In the history of exegesis, the book's (supposed) author has often been regarded as mad or ill, or as suffering from \'Post-Traumatic Stress Disorder\' according to a recent diagnosis. The present study radicalizes this approach by investigating the book of Ezekiel as trauma literature. On the basis of a multi-faceted trauma hermeneutics the peculiarities as well as the inconsistencies of the book are shown to be material aspects of a fictionalised trauma process in the context of Israel's experiences of siege warfare and mass deportation in the early 6th century bce. The analysis demonstrates that the potential for violence inherent in the catastrophe has created not only an intense discourse about blame and punishment but also a theologically disturbing picture of a traumatized deity; in both cases the purpose is to assure the survival of Yhwh and the people. Das Ezechielbuch hat seine Leserschaft seit jeher verwundert und verwirrt. Den vermeintlichen Autor des Buches hat man im Laufe der Auslegungsgeschichte immer wieder pathologisiert - zuletzt ist Ezechiel mehrfach die Diagnose "Posttraumatische Belastungsstörung" attestiert worden. Die vorliegende Studie nimmt diesen Krankheitsansatz auf und radikalisiert ihn, indem sie das Ezechielbuch konsequent als fiktionale Trauma-Literatur analysiert. Vor dem Hintergrund einer mehrdimensionalen Trauma-Hermeneutik erschließt sie die Ezechielprophetie neu als literarisch-theologische Auseinandersetzung mit den traumatisierenden Kriegsereignissen, die Juda und Jerusalem zu Beginn des 6. Jh.s volumeu.Z. getroffen haben. Es zeigt sich, dass die ungeheure Gewaltfülle der Exilskatastrophe nicht nur einen massiven Schuld-Strafe-Diskurs, sondern auch das theologisch erschütternde Bild einer traumatisierten Gottheit aus sich herausgesetzt hat - beides mit dem Ziel, das Überleben JHWHs und des Volkes zu sichern.